Regulatory Mechanism and Experimental Verification of Patchouli Alcohol on Gastric Cancer Cell Based on Network Pharmacology - Song, Yanru; Chang, Liang; Wang, Xiaoyuan; Tan, Bibo; Li, Jianbo; Zhang, Jie; Zhang, Fengbin; Zhao, Lianmei; Liu, Guangjie; Huo, Bingjie (Frontiers in Oncology, 2021)
Background: Pogostemon cablin is a traditional Chinese medicine (TCM) that is frequently used to treat various gastrointestinal diseases. Patchouli alcohol (PA), a compound extracted from the Pogostemon cablin, has been shown to have anti-tumor efficacy in human colorectal cancer. However, the mechanism of PA's anticancer effect on gastric cancer (GC) remains unknown. Methods: We used the public database to obtain the potential targets of PA and genes related to GC. Bioinformatic analyses, such as the Kyoto Encyclopedia of Genes and Genomes (KEGG), Gene Ontology (GO), and protein-protein interactions (PPI), were used for analyzing the potential signal pathways and targets. Cell experiments were also conducted to further explain the impact and molecular mechanism of PA on GC, as well as to confirm the findings of network pharmacology. Results: Using network pharmacological analysis, 161 possible targets were identified for the treatment of GC. Network analysis and functional enrichment analysis show that PA produced a marked effect in the treatment of GC through multi-targets and multi-pathways, especially the MAPK and PI3K/AKT signal pathways. In addition, PA showed the inhibition of GC cell proliferation, migration and invasion in cell experiments. According to our findings, PA could also cause G0/G1 phase arrest and apoptosis in GC cells. Conclusion: Using network pharmacology, we aim to uncover the possible molecular mechanism of PA on GC treatment in this research. Cell experiments were also conducted to confirm the therapeutic effect of PA on GC.